The Story in Fiction and Film of French Collaboration in the Occupation and Complicity in the Holocaust (1940-1944) : German Occupation, Vichy, and Truth - Schwarz, Daniel R. (Jews, Judaism, and the Arts., 2025)
This book examines fiction and film narratives that show the active collaboration of the Vichy government with the Nazis in the deportation and murder of the Jews of France. It also explains how these fiction and film narratives affected the official and dominant historical narrative of the 1940-44 Occupation years. More than anything, what changed the dominant narrative of the Occupation years are documentaries and creative works which imaginatively selected and arranged the presentation of neglected and suppressed facts. By stressing how documentaries, novels, and imaginative films changed the dominant narrative of 1940-1944, the author is also arguing how cultural production transformed history.